Influence of Continuous Nursing on the Psychological State and Coping Style of Patients Undergoing Pacemaker Implantation - Xin LIU; Xu HE; Ling LI; Lili HUANG; Zhaojun LIU (Tehran University of Medical Sciences, 2015)
Background: Patients undergoing pacemaker implantation often experience anxiety and fear. As such, studies have focused on the mechanisms that relieve the negative emotions caused by the intervention. Continuous nursing is a safe and effective nursing mode. In this study, continuous nursing intervention was provided for elderly patients undergo-ing pacemaker implantation and an empirical investigation was performed to determine the effects of their negative emotion and disease-coping ability. Methods: Overall, 114 (68 males and 46 females) elderly patients who were undergoing pacemaker implantation from Harbin City (China), were enrolled in the study. The patients were divided into two groups, namely, the control group and the intervention group, based on different nursing methods. Routine nursing was applied to the control group; continuous nursing support was provided for the intervention group from January 2014 to January 2015. The nursing results of the two groups were compared. These results were also evaluated using self-rating depression scale, self-rating anxiety scale, and trait coping style questionnaire. Result: The effects of depression and anxiety intervention were significant in the intervention group (P<0.05). Com-pared with the control group, the intervention group did not significantly differ. The coping style of the intervention group elicited significant effects. Compared with the control group, the intervention group was significantly different (P < 0.05). Conclusion: Continuous nursing can relieve the negative emotion and improve the negative coping style of patients undergoing pacemaker implantation.